GROWTH PERFORMANCE OF FRIESWAL CALVES UNDER DIFFERENT FLOORS (Indian Journal of Animal Production and Management, 2013)
The data on Thirty Frieswal calves (15 male and 15 female) maintained at Military dairy farm, Mhow District Indore (M.P). were utilized to study the growth performance frieswal calves under three floor types ,namely Concrete floor, Concrete floor with straw beddings and Earthen (Kachha) floor with 10 calves (5male + 5 female) in each group. In general Average Daily Gain(ADG) showed increasing trend with advancement of age and the respective average daily gains during 13th week of age were 416.11±28.65, 498.11±25.39 and 481.11±25.29 gram. At 9th and 10th week of age i.e. just after closing of milk feeding ADG was decreased however, in subsequent weeks, calves regained their weight gain. Analysis of variance for heart girth and height at wither indicated that upto 3rd fortnight interval there was no significant difference among floor types. However, subsequently from fourth fortnight interval there was a significant (P
Keywords: Frieswal calves; floor types; growth performance